1979
DOI: 10.1042/bj1770887
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of thiamin-binding protein from chicken egg white

Abstract: A thiamin-binding protein was isolated and characterized from chicken egg white by affinity chromatography on thiamin pyrophosphate coupled to aminoethyl-Sepharose. The high specificity of interaction between the thiamin-binding protein and the riboflavin-binding protein of the egg white, with a protein/protein molar ratio of 1.0, led to the development of an alternative procedure that used the riboflavin-binding protein immobilized on CNBr-activated Sepharose as the affinity matrix. The thiamin-binding protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 31 publications
3
26
0
Order By: Relevance
“…The exact function of these thiamine binding proteins in microorganisms is still unknown, however, evidence for their involvement in thiamine transport has been discussed (7). Recently , some thiamine binding proteins have been found in animal tissues such as chicken egg white (8) and liver (9), and it has been supposed that the binding protein in chicken egg white has a role in the deposition and transport of thiamine for the proper growth and development of chick embryo. On the other hand, a previous communication from this laboratory has indicated that there exists a thiamine-binding protein in rice bran, which was the first observation made on a plant (10) (Osaka).…”
Section: Discussionmentioning
confidence: 99%
“…The exact function of these thiamine binding proteins in microorganisms is still unknown, however, evidence for their involvement in thiamine transport has been discussed (7). Recently , some thiamine binding proteins have been found in animal tissues such as chicken egg white (8) and liver (9), and it has been supposed that the binding protein in chicken egg white has a role in the deposition and transport of thiamine for the proper growth and development of chick embryo. On the other hand, a previous communication from this laboratory has indicated that there exists a thiamine-binding protein in rice bran, which was the first observation made on a plant (10) (Osaka).…”
Section: Discussionmentioning
confidence: 99%
“…Thiamin‐binding proteins (TBPs) found in plant seeds bind only free thiamin and are assumed to be seed storage proteins because of their localization in plant seeds (Nishimura et al 1984a), although the TBPs from microorganisms and animal tissues bind both free thiamin and thiamin phosphates and are involved in thiamin transport (Iwashima et al 1979; Muniyamppa and Adiga 1979). Sesame seeds have two 17‐kDa TBPs, termed STBP‐I and ‐II, and a 19‐kDa TBP, termed STBP‐III (Shimizu et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…They were exposed to a 14h-0h light-dark schedule. The sources of other biochemicals and reagents were detailed elsewhere (Muniyappa & Adiga, 1979).…”
Section: Methodsmentioning
confidence: 99%